Model Rancangan Pengelolaan Manajemen Risiko pada PT. XYZ Menggunakan ISO 31000 - M. Rezky Iqbal P. (Majalah Ilmiah Bijak, 2017)
Heavy equipment trading industry is an industry that has a high level of risk. The heavy equipment trading industry is influenced by several factors that determine the condition of the mining industry, the condition of the property industry, the forestry industry and the price of the world's coal commodities. Segmentation to heavy equipment unit is very focused on the company because the heavy equipment unit has a high risk. When viewed from the impact of the impact of the industry is highly a requirement of risk. In accepting and managing these risks, it is necessary to apply risk management with the objective to minimize the risk of loss to the company.